Potential Plant Utilization in the Agroforestry System of Tectona grandis (Teak) and Plukenetia volubilis (Sacha inchi) - H P, Reggina; Masyithoh, Galuh; Supriyadi, Supriyadi; Novarika, Risa; Murhofiq, Sigit (Agro Bali : Agricultural Journal, 2025)
Agroforestry systems represent an approach to forest management that considers both ecological and economic functions. The system aims to optimize land use by integrating forest and agricultural components, thereby enhancing the economic and ecological benefits of the forest area. Consequently, information regarding the potential of agroforestry is essential for designing an effective management strategy. One location implementing agroforestry systems is Banyurip Village, which features an uncommon combination of key plants, namely Tectona grandis and Plukenetia volubilis. Banyurip has been selected as the research location due to its unique circumstances; most other locations primarily focus on the cultivation of sacha inchi plants, and there is a notable absence of agroforestry system applications. This presents an opportunity to explore and assess the potential benefits of integrating agroforestry practices in this area. The aims of this research is to provide information about the potential utilization of plant species present in the study area, utilizing data collection methods through interviews. Informants were selected purposively based on the criteria of farmers practicing an agroforestry system that focuses on a combination of teak and sacha inchi in production forest areas. Six farmers participated as research informants. This research was conducted in production forests managed by Perum Perhutani, employing a methodology that includes an exploratory descriptive approach accompanied by field observations and interviews. The results identified sacha inchi as the primary supporting plant species and 11 other cultivated plant species, with a total of 37 associated plant species, consisting of 10 woody plant species and 27 non-woody plant species. The identified plant types possess economic and ecological potential, such as teak, which serves as an oxygen producer, and sacha inchi, which holds significant economic value due to its oil.